Gender, unpaid labour and economics - Zachorowska-Mazurkiewicz, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Unpaid labour, including care labour is mostly performed by women. Economic theories explain differences in allocation of time between women and men in various ways – neoclassical theories point to the rational choice associated with the varying efficiency of women and men both in the labour market and in the household, while heterodox theories point to the influence of norms, social values and traditions, according to which the man is the breadwinner and the woman the caregiver. Unpaid labour is often called home duties or responsibilities, and even though it is very difficult, tiring and demanding, it is not valued and respected. The main objective of this paper is to present the importance of unpaid care work in the economy and propose the reconsideration of economic policies.